2022
DOI: 10.1111/jfbc.14439
|View full text |Cite
|
Sign up to set email alerts
|

Flavor formation based on lipid in meat and meat products: A review

Abstract: Meat product is popular throughout the world due to its unique taste. Flavor is one of the most important quality characteristics of meat products and also is a key influencing factor in the overall acceptability of meat products. The flavor of meat products is formed by precursors undergoing a series of complex reactions. During meat product processing, lipids are hydrolyzed by lipase to produce flavor precursors such as free fatty acid, then further oxidized to form volatile flavor compounds. This review sum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(19 citation statements)
references
References 186 publications
(175 reference statements)
0
11
0
Order By: Relevance
“…The addition of GTE seemed to increase the decanal concentration, but had no significant effect on hexanal, while it decreased the concentration of other aldehydes in EWP. As reported, these long‐chain saturated linear aldehydes were normally considered as lipid oxidant products 26 . The release mechanism of the long‐chain aldehydes in a simple protein system has rarely been reported so far.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The addition of GTE seemed to increase the decanal concentration, but had no significant effect on hexanal, while it decreased the concentration of other aldehydes in EWP. As reported, these long‐chain saturated linear aldehydes were normally considered as lipid oxidant products 26 . The release mechanism of the long‐chain aldehydes in a simple protein system has rarely been reported so far.…”
Section: Resultsmentioning
confidence: 99%
“…As reported, these longchain saturated linear aldehydes were normally considered as lipid oxidant products. 26 The release mechanism of the long-chain aldehydes in a simple protein system has rarely been reported so far. Egg white is a high protein system with no lipid content, thus the long-chain saturated linear aldehydes in EWP maybe actually formed from egg yolk, then the formed aldehydes were captured by EW protein.…”
Section: Identification Of Volatile Compoundsmentioning
confidence: 99%
“…Generally speaking, the quality of meat mainly depends on the related changes in proteins [ 24 ] and lipids [ 25 ]. Lipid oxidation may affect meat quality by affecting the formation of flavor compounds in meat [ 26 ], while proteins and amino acids may play important roles as flavor precursors [ 27 ] and may also affect the taste, tenderness, and water retention of meat [ 28 ]. In addition, the degradation of proteins and fats produces alkaline nitrogen-containing substances, leading to an increase in the TVB-N and pH [ 21 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, whether changes in metabolites affect duck meat quality was explored in the current study. Some studies have reported that it is vital for the content of nucleotides and their derivatives to change in fresh meat to improve flavor precursors, which may affect the taste, tenderness, and water-holding capacity of meat ( Xiao et al, 2019 ; Fu et al, 2022 ). In the present study, the guanosine content in the D900 group was significantly lower than those in the D60 and D300 groups, which was consistent with a previous study that found that the guanosine content in meat is highly correlated with flavor, and meat with lower guanosine content has a higher quality ( Tikk et al, 2006 ; Muroya et al, 2019 ).…”
Section: Disscussionmentioning
confidence: 99%